The effect of the level of the undergraduate nursing students toward the elderly - LOK, Neslihan; GUL, Humeyra; SAKINMAZ, Esma; KESKIN, Mustafa; SISEK Seyma AYDIN, Yener (Innovational: Journal of Nursing and Healthcare, 2024)
Objective: Competences provided nursing education students, also affects their approach and sensitivity for the elderly, a special group. The effect of attitudes towards older students' level therefore the nursing research and education at the undergraduate level were investigated. Materials and methods: The study descriptive relational type, formed the study sample Mediterranean University studying in the first and last class of 371 nursing students. Data, "Socio-Demographic Information Form" and "Attitude Scale for the Elderly" were collected using in the classroom. Number of percentage distributions for the evaluation of data and MannWhitney U and Kruskal-Wallis test was used. Results: The mean age of 20.06 ± 2.15 students who agreed to participate in the study, 67.9% of girls and 66.3% of first class, grew up in a nuclear family, 76.3%, 41.5% of the longest in the Mediterranean region, 42.6% lived in the city for a long time and lived in the same house with a period of life of older individuals was 64.4%. First of classes in the field of education for the elderly attitude scale mean score 142.67 ± 7.34, while the last class in the field of education for the elderly attitude scale is the average score of 176.58 ± 6.46 difference was statistically significant (p = 0.016). Conclusion: In this study, the nursing education at the undergraduate level, students have seen a positive impact on their attitudes toward the elderly. The girl is in terms of variables, those living in extended families, who spend a large part of his life in East and South East Anatolia, after those who lived through any period of elderly life and graduation attitudes towards older people who want to work with the elderly are affected positively.